Additive neurogenesis supported by multiple stem cell populations mediates adult spinal cord development: A spatiotemporal statistical mapping analysis in a teleost model of indeterminate growth. Issue 11 (23rd July 2017) - Sîrbulescu, Ruxandra F.; Ilieş, Iulian; Meyer, Annette; Zupanc, Günther K.H.
ABSTRACT: The knifefish Apteronotus leptorhynchus exhibits indeterminate growth throughout adulthood. This phenomenon extends to the spinal cord, presumably through the continuous addition of new neurons and glial cells. However, little is known about the developmental dynamics of cells added during adult growth. The present work characterizes the structural and functional development of the adult spinal cord in this model organism through a comprehensive quantitative analysis of the spatial and temporal dynamics of new cells at various developmental stages. This analysis, based on a novel statistical mapping approach, revealed within the adult spinal cord a wide distribution of both mitotically active and quiescent Sox2‐expressing stem/progenitor cells (SPCs). While such cells are particularly concentrated within the ependymal layer near the central canal, the majority of them reside in the parenchyma, resembling the distribution of SPCs observed in the mammalian spinal cord. The active SPCs in the adult knifefish spinal cord give rise to transit amplifying progenitor cells that undergo a few additional mitotic divisions before developing into Hu C/D+ neurons and S100+ glial cells. There is no evidence of long‐distance migration of the newborn cells. The persistence of cell proliferation and differentiation, combined with low levels of apoptosis, leads to a continuous addition of cells to the existing tissue. Newly generated neurons have functional and behavioral relevance, as indicated by the integration of axons of new electromotor neurons into the electric organ of these weakly electric fish. This results in a gradual increase in the amplitude of the electric organ discharge during adult development. © 2017 Wiley Periodicals, Inc. Develop Neurobiol 77: 1269–1307, 2017